Abiotic Stress Plant Responses and Applications in Agriculture - Vahdati, Kourosh; Leslie, Charles (IntechOpen, 2013)
"This book is not intended to cover all known abiotic stresses or every possible technique used to understand plant tolerance but, instead, to describe some of the widely used approaches to addressing such major abiotic stresses as drought, salinity, extreme temperature, cold, light, calcareous soils, excessive irradiation, ozone, ultraviolet radiation, and flooding, and to describe major or newly emerging techniques employed in understanding and improving plant tolerance. Among the strategies for plant stress survival, examples of both avoidance and tolerance are presented in detail and comprehensive case studies of progress and directions in several agricultural crops such as apple, walnut, grape and wheat are included."